2017
DOI: 10.1002/gps.4715
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a Geriatric Depression Scale cutoff based upon quality of life: a population‐based study

Abstract: Objectives: The cutoff scores for the Geriatric Depression Scale (GDS) commonly adopted in clinical and research settings are based upon other neuropsychological tests. However, any intervention for depression should aim at improving subjective quality of life (QoL). We searched for a GDS cutoff level that might identify a decrease in perceived QoL using a scale that also allows formal cost-effectiveness calculations. Methods: Quality of life was assessed by the Health Utilities Index, Mark 3 in all 344 reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…He also found that physical morbidity and impaired level of functioning were associated with depression [4]. Alice Laudisio pointed out that depressive symptoms were associated with reduced Qol [14]. This may be because the physical illness affects mental health and therefore increases the risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…He also found that physical morbidity and impaired level of functioning were associated with depression [4]. Alice Laudisio pointed out that depressive symptoms were associated with reduced Qol [14]. This may be because the physical illness affects mental health and therefore increases the risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…He also found that physical morbidity and impaired level of functioning were associated with depression [3] . Alice Laudisio pointed out that depressive symptoms were associated with reduced Qol [13] . This may be because the physical illness affects mental health and therefore increases the risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Education level was evaluated using the sum of completed years at school, high school or college, and defined as primary or less (≤6 years), secondary (high school or similar: 6 to ≤12 years) and college or university (college or university degree: >12 years of education). Depression and depressive symptoms were measured using the Geriatric Depression Scale (GDS), 17 with a total point score ranging from 0 to 15, and a total score of >5 points was used to indicate depression 18 . Health perception was self‐assessed by patients indicating their current state of health using a visual analogue scale (VAS) ranging from 0 (worst) to 100 (best).…”
Section: Methodsmentioning
confidence: 99%